Função colinérgica do núcleo do trato solitário comissural nas respostas cardiorrespiratórias à hipóxia e hipercapnia - Furuya, Werner Issao (Universidade Federal de São Carlos, 2017)
The nucleus of the solitary tract (NTS) is the primary site of visceral afferents, such as baroreceptors and arterial chemoreceptors. Recent data from our laboratory have shown that the microinjection of acetylcholine (ACh) into the commissural moiety of the NTS (cNTS) of decorticated arterially-perfused in situ preparations of male juvenile rats did not change the sympathetic nerve activity (SNA), but increased the phrenic nerve activity (PNA). Furthermore, we demonstrated that the ACh-induced responses in cNTS involve the activation of both nicotinic and muscarinic receptors. However, nicotinic receptors seem to play a more relevant role in the control of breathing, especially considering that such receptor antagonism promotes a decrease in the KCN- activated peripheral chemoreflex tachypneic response. However, the effects of specific nicotinic and muscarinic agonists in the cNTS on respiratory and sympathetic responses have not been studied yet. Once established the involvement of nicotinic receptors in the cNTS on peripheral chemoreflex ventilatory responses activated by cytotoxic hypoxia (KCN), we also evaluated the involvement of the cholinergic system in the cNTS on respiratory and sympathetic responses induced by hypercapnia or 24 h sustained hypoxia. Therefore, this project proposed to study the effects of selective activation of distinct cholinergic receptors in the cNTS on respiratory and sympathetic activities and the role of the cholinergic system in cNTS on sympathetic and respiratory activities reflex changes in response to hypercapnia or sustained hypoxia. We observed that the injection of both nicotinic and muscarinic agonists in the cNTS induces an increase in SNA and changes in the respiratory modulation pattern. The nicotinic agonist induces a decrease in respiratory frequency, as well as the blockade of the enzyme acetylcholinesterase. It was also observed that the cholinergic agonists promote an increase in the amplitude and duration of the pre-inspiratory (pre-I) period of the hypoglossal nerve and also increased the amplitude of the vagus nerve. When it comes on the protocols involving hypoxia, we observed that the cholinergic antagonists injected into the cNTS of rats previously exposed to hypoxia promoted a decrease in sympathetic activity, increased respiratory frequency, decreased hypoglossal nerve amplitude, and decreased post-inspiratory peak amplitude of the vagus nerve, but only the muscarinic antagonist decreased phrenic nerve amplitude and hypoxia-induced hypoglossal nerve pre-I increase. Regarding to the experiments with hypercapnia, we verified that the nicotinic antagonist in the cNTS inhibited the hypercapnia-induced increase in pre-I of the hypoglossal nerve. In addition, the nicotinic antagonist injected into the cNTS also potentiated the recruitment of late-E activity from the abdominal nerve. Taken together, the responses observed with the cholinergic agonists and injected into the cNTS, as well as the antagonists upon hypoxia, suggest the involvement of cholinergic pathways in the cNTS in the modulation of sympathetic and respiratory responses to sustained hypoxia. On the other hand, it seems that only nicotinic receptors in the cNTS are involved in hypercapnia-induced increase in pre-inspiratory activity and active expiration.
Keywords: Acetilcolina; Atividade simpática; Atividade respiratória; Quimiorreceptores; Núcleo do trato solitário; Bulbo; Acetylcholine; Sympathetic nerve activity; Respiratory activity; Chemoreceptors; Nucleus of the solitary tract; Brainstem; CIENCIAS BIOLOGICAS::FISIOLOGIA